Mechanical behavior of external root resorption cavities restored with different materials: a 3D-FEA study - H. Akgün; E. Kalyoncuoğlu (BMC Oral Health)
Abstract Background The aim was to evaluate the stresses in teeth, with external root resorption (ERR) restored with different materials using finite element analysis (FEA). Methods In this study, a Micro-CT scan was conducted on a prepared maxillary central tooth. DICOM-compatible images obtained from the sections were converted into stereolithography format using Ctan software. Utilizing the VRMesh Studio program, a solid model was generated based on the 3D image obtained through micro-CT scanning. External root resorption cavities were strategically designed at the apical, middle, and coronal thirds levels on the buccal surface of the tooth root. Subsequently, these created resorption cavities were restored using Biodentin, mineral trioxide aggregate (MTA), and glass ionomer cement (GIC). The models were devided into 12 groups according to their location,the type of restoration, material used and the null group was added. To allow measurement of Von Mises stress values, a simulated oblique force of 100 N, was applied directed towards the palatal region of the upper central tooth at a 45° angle to the occlusal plane. Results The highest von Mises stress value in the dentin was observed in the unrestored coronal cavity model (99.00 MPa). FEA results demonstrated that using a repair material significantly reduced the stress levels in the dentin. The lowest stress values were seen in cavities restored with Biodentine. The stress values in cavities treated with Biodentine and MTA were found to be similar. Conclusions Restoring the external resorption cavity in the tooth significantly reduced stress levels in the dentin. Biodentine and MTA absorbed more force, transmitting less stress to the dentin compared to GIC. Clinical relevance Biodentin and MTA can be used in the repair of external resorption cavities.